UPAYA GURU PAI DALAM MENCEGAH PERGAULAN MENYIMPANG REMAJA - Fitriah Zahara; Hasan Matsum (PAI RAFAH, 2023)
Juvenile delinquency can include a variety of behaviors, such as vandalism, theft, substance abuse, gang involvement, absenteeism, or violent behavior. Many factors contribute to juvenile delinquency, including socioeconomic status, family dynamics, peer influences, educational issues, and exposure to violence or crime in society. Personal factors such as psychological, emotional, or behavioral problems may also play a role. This study focuses on the main issue, which is the efforts of Islamic religious education teachers to prevent associations that exclude teenagers at Medan National Heroic Middle School. This study aims to achieve two goals: (1) explore the efforts of teachers in Islamic religious education to prevent students from committing crimes in school, and (2) identify factors that aid or hinder teachers' efforts to remediate students' delinquency. The implications of this study indicate that the efforts of Islamic religious education teachers at Medan National Heroic Middle School have been ineffective in redressing student delinquency. Therefore, it is suggested that these teachers strengthen their tutoring work so that they fulfill their responsibilities in moral training for students. Based on the information provided, it appears that this study is aimed at addressing the role of Islamic Religious Education teachers in addressing student delinquency and implementing necessary remedial strategies needed to deal with this problem effectively.